Long-term disability after blunt chest trauma: Don't miss chronic neuropathic pain!. Issue 1 (January 2019) - Carrie, Cedric; Guemmar, Yassine; Cottenceau, Vincent; de Molliens, Louis; Petit, Laurent; Sztark, Francois; Biais, Matthieu
Highlights: Chronic pain and long-term respiratory disability are very common after severe blunt chest trauma patients. Neuropathic pain is frequently under-diagnosed and responsible for significant impairment of quality of life. A thoracic trauma severity score ≥12 is associated with the occurrence of neuropathic pain at 3 months. Abstract: Introduction The main objective of this prospective study was to assess the incidence of chronic pain and long-term respiratory disability in a single-center cohort of severe blunt chest trauma patients. Methods Over a 10-month period, all consecutive blunt chest trauma patients admitted in Intensive Care Unit (ICU) were screened to participate in a 3-month and 12-month follow-up. The following variables were prospectively assessed: persistence of chronic chest pain requiring regular used of analgesics, neuropathic pain, respiratory disability, physical and mental health status. Univariate and multivariable analysis were conducted to assess variables associated with chronic chest pain, neuropathic chest pain and respiratory disability. Results During the study period, 65 patients were included in the study. Chronic chest pain and respiratory disability were reported in 62% and 57% of patients respectively at 3 months postinjury. Neuropathic pain was reported in 22% of patients, associated with higher impairment of quality of life. A thoracic trauma severity score ≥12 and a pain score ≥4 at SICU discharge were the only variables significantly associated with the occurrence of neuropathic pain at 3 months (OR = 7 [2–32], p = 0.01 and OR = 16 [4–70], p < 0.0001 ). Conclusion According to the current study, chronic pain and long-term respiratory disability are very common after severe blunt chest trauma patients. Special attention should be paid to neuropathic pain, frequently under-diagnosed and responsible for significant impairment of quality of life.